Internet communications of military personnel and their families in social networks as an object of digital sociology’s study - N. V. Il’ina; Yu. Yu. Sukhovskaya (Цифровая социология)
The conceptual, methodological and technological approaches to organization of sociological study of communicative Internet activity ofmilitary personnel in a social networks, the specific behavior in accordance with the requirements as to members ofthe militaryprofessional corporate group of people in the information-communication network “Internet” have been considered. The constitutional norms that restrict the rights of military personnel in various spheres of social interaction, as well as the norms of domestic legislation that specify these requirements have been analyzed. The described type of Internet communication has been characterized as an object of study of military sociology at various levels: general scientific, private scientific and empirical. The author's found a connection between a considered problem with the concepts of “information society”, “digital society”, “digital economy” and virtualization of social relations, as well as the concept of “human rights”. The general tendency to include of various countries confrontation with a likely enemy in the virtual space in the military- doctrinal documents has been revealed. At the same time, ensuring military security involves protecting the minds of their military personnel from negative impact, including in the case of their use of services in the Internet space. The experience of other countries in regulating the social activity of military personnel and their families in the Internet has been described. Based on the generalization of social practice, conclusions from the risk analysis of the participation of subjects of military professional activity in social networks, which is associated with threats to determine the location of military units, plans for the movement of troops, weapons, staff and personnel, that is, information constituting a military secret, have been presented. A list of other threats related to social communications of military personnel and their families in the virtual space also has been adduced. The ways to reduce the risk of negative impact on military members and their families participate in social networks and other Internet communications by implementing legal, organizational and outreach activities have been presented.